An examination of selected works for concert band and chamber ensemble: Fanfare Héroïque by Eugéne Bozza, Symphonic Sketch by Charles Carter, and Tempered Steel by Charles Rochester Young - Cook, Alexander Aaron (Kansas State University, 2016)
This report possesses a detailed analysis of three works, two works for concert band and one for brass ensemble. The works included in this report are Fanfare Héroïque (1944) by Eugéne Bozza, Symphonic Sketch (1994) by Charles Carter, and Tempered Steel 2nd ed. (1997 and 2008) by Charles Rochester Young. Also included in this report is performance information about the pieces above, the author’s thoughts about the role of music education in the American school system, and a section that discusses quality literature for concert ensembles. It is the author's hope that some of this information is used to aid teachers in their study of these works in order to be more effective in the classroom. In order to facilitate this, each analysis includes biographical information about the composer, historical information about the composition, technical information, musical information, an analysis of form, and sample lesson plans with reflections.
Keywords: Carter Young Bozza Brass Band Report